Performance of Y0.9Sr0.1Cr0.9Fe0.1O3−δ as a sulfur-tolerant anode material for intermediate temperate solid oxide fuel cells - Bu, Yun-Fei; Zhong, Qin; Xu, Dan-Dan; Zhao, Xiao-Lu; Tan, Wen-Yi (Journal of power sources, 2014)
Perovskite-type Y0.9Sr0.1Cr0.9Fe0.1O3−δ maintained good chemical stability under a H2S-containing atmosphere based on results from X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FT-IR) in our previous study. In this research, the YSCF-based anode was studied using H2 and H2S-containing fuels. The activity of an electrode is closely related to its material composition, lattice structure, physic-chemical properties, and morphologic structure. Therefore, the characteristics of the YSCF powders and the cell were analyzed by XRD, Brunauer–Emmett–Teller (BET) surface area analysis, and scanning electron microscopy (SEM). The conductivities of YSCF were evaluated by four-probe method in 10% H2–N2, 1% H2S–N2 and air, respectively. Thermodynamic calculations and X-ray photoelectron spectroscopy (XPS) analysis have been used to investigate the stability of the elements in YSCF upon exposure to hydrogen sulfide (H2S) in hydrogen (H2) over a range of partial pressures of sulfur (pS2) and oxygen (pO2) that are representative of fuel cell operating conditions. In addition, the performance of the complete cell (YSCF–SDC|SDC|Ag) under H2S and H2 fuel mixtures was also evaluated by electrochemical impedance spectra (EIS) and I–V and I–P curves. The emergence of FeSO4 in the sulfur treatment should play an important role in preventing further sulfur-poisoning. [Display omitted] The Y0.9Sr0.1Cr0.9Fe0.1O3−δ was synthesized by gel combustion method. The YSCF-based anode was studied for further research as the real anode for SOFC operating on H2S or H2S-containing fuels. The characteristic of YSCF powders and the cell were analysis by XRD, BET, and EIS. It appeared to be chemically and electrochemically stable under SOFC operating conditions. Thermodynamic calculations and X-ray photoelectron spectroscopy (XPS) analysis have been used to research the stability of the element in YSCF when exposed to hydrogen sulphide (H2S) in hydrogen (H2) over a range of partial pressures of sulfur (pS2) and oxygen (pO2) representative of fuel cell operating conditions. By using analysis of electrochemical performance and XPS, the emergence of FeSO4 in the sulfur treatment should play an important role to prevent further sulfur-poisoning. •Y0.9Sr0.1Cr0.9Fe0.1O3−δ as an anode material for SOFC was examined.•YSCF was an active anode for the oxidation of the H2S-containing fuel.•YSCF was tested by EIS under different gas environment as an SOFC anode.